(untitled) (Spectrum of Humanities and Social Sciences, 2025)
Understanding the local communities’ attitudes toward conservation areas is crucial to conservation area management planning. However, what socio-economic and demographic factors drive their attitude. The objective of this study is to determine the status of awareness of Dallagaun people and their attitudes towards wildlife and its conservation. Survey design method was used having 126 households of that community and descriptive statistics was used to analyze the data. Findings reveal that Community demonstrates positive perception and attitude towards wildlife conservation recognizing its ecological, economic, and social value. Conservation helps maintain ecological balance, supports future generations, and contributes to local economic growth and wildlife-based tourism, with the highest support (Mean: 3.92) shown for inclusive policy participation, actual participation in conservation programs and willingness to volunteer are relatively lower, indicating a gap between support and engagement, There is a clear desire for increased community involvement in conservation decisions, which presents a valuable opportunity to enhance participation through inclusive, benefit-sharing, and education-driven strategies, ensuring that local voices are central to wildlife policy and practice.